Evidence That a Precursor Glycoprotein Is Cleaved to Yield the Major Glycoprotein of Avian Tumor Virus - England, James M. (1977)
A glycoprotein designated pr90, which is recognized by anti-gp85 serum, is present in lysates of pulse-labeled transformed cells. Under chase conditions, a reduction in the level of labeled pr90 is observed concomitant with the appearance of labeled, cell-associated viral glycoprotein.